Strategi Pencegahan Hipertensi Pada Populasi Lansia Melalui Edukasi Gizi Dan Pemeriksaan Tekanan Darah - Alfred Sutrisno Sim; Alexander Halim Santoso; Farell Christian Gunaidi; Kasvana; Nikita; Sylvia Cendy Enike (CV. Akira Java Bulu, 2025)
Hypertension is a major health problem in the elderly that contributes to an increased risk of morbidity and mortality due to cardiovascular disease and other complications. Early detection of hypertension is very important to prevent serious complications and improve the quality of life of the elderly. This community service activity was carried out at Panti Werdha Hana, Babakan, South Tangerang, involving 36 elderly people (7 men and 29 women). The methods used included socialization about hypertension and the importance of early detection, as well as blood pressure screening using a calibrated digital tensiometer. The screening results showed that 22.22% of participants had hypertension, 63.89% pre-hypertension, and 13.89% had normal blood pressure. Education about healthy lifestyle modifications was given to participants who were at risk or had hypertension. This activity emphasized the importance of blood pressure screening and education as a strategy to prevent hypertension in the elderly. With early detection and appropriate intervention, the risk of hypertension complications can be minimized so that the quality of life of the elderly increases. Keywords: Hypertension, Blood Pressure, Education, Screening, Elderly